Minimally invasive surgical treatment for large impacted upper ureteral stones: Ureteroscopic lithotripsy or percutaneous nephrolithotomy? - Bozkurt, Ibrahim Halil; Yonguc, Tarik; Arslan, Burak; Degirmenci, Tansu; Gunlusoy, Bulent; Aydogdu, Ozgu; Koras, Omer (Canadian Urological Association Journal, 2015)
Introduction: The management of patients with large impacted upper ureteral stones is difficult; there is no standard treatment. We compared the outcomes of percutaneous nephrolithotomy (PCNL) and ureteroscopic lithotripsy (UL) to treat large (≥1.5 cm), impacted, upper ureteral stones. Methods: In total, 86 patients with large impacted upper ureteral stones were included in this study. Of these patients 41 underwent UL and 45 underwent PCNL. The inclusion criteria were: longest diameter of stone ≥1.5 cm, the localization of stone between the lower border of L4 spine and ureteropelvic junction and impacted stone. Results: In the UL group, we were unable to reach the stone in 3 patients because of ureteral stricture and edema despite balloon dilation. Of these 3 patients, we were unable to optimally visualize the stone in 2 patients due to bleeding and mucosal injury following balloon dilation. The stricture was too firm and could not be passed in the third patient. Also in the UL group, 15 patients had stones or big fragments which migrated into the renal collecting system. In the PCNL group, 21 patients had concurrent renal stones <1 cm and stones were successfully removed in all patients. No statistically significant difference was found between groups in terms of operation time. Mean hospital stay was significantly shorter in the UL group. Success rates were 82.3% in the UL group and 97.6% in the PCNL group (p = 0.001). Conclusion: The recent study confirms that PCNL is a safe and effective minimally invasive procedure with acceptable complication rates in the treatment of patients with large, impacted upper ureteral stones.